Exploring Academic Writing and Voice in ESL Writing. - Correa, Doris (Íkala, Revista de Lenguaje y Cultura, 2009)
This literature review explores two basic questions: First, why have English as a Second Language (ESL)/English as a Foreign Language (EFL) academic writing courses not been able to signiﬁcantly help ESL/EFL students meet the academic writing demands of their university courses? Second, how can ESL/EFL writing instructors better help these students succeed in their undergraduate courses? To respond to these questions, the author reviews how notions of academic writing, text, and voice have changed over time, and how these changes have inﬂuenced (ESL) and (EFL) writing approaches and methodologies. The author also presents some of the critiques that scholars have posed regarding each of these notions, approaches and methodologies, and draws some conclusions based on these critiques. Received: 13-11-07 / Accepted: 08-12-08 How to reference this article: Correa, D. (2009). Exploring Academic Writing and Voice in ESL Writing.Íkala. 14(1), pp.103-132.